The Influence of Job Satisfaction, Compensation, Work Environment, Work Hour Delays, and Organizational Culture on Employee Performance at Pudam Tirtabina Labuhanbatu Regency - Yuliani Pohan; Siti Lam'ah Nasution; Aulia Indra (Journal of Global Islamic Economic Studies, 2025)
This study aims to analyze the influence of Job Satisfaction, Compensation, Work Environment, Work Hour Delays, and Organizational Culture on Employee Performance at Pudam Tirtabina, Labuhanbatu Regency. The data collection techniques used in the research are observation, documentation, and questionnaires using a Likert scale. The population in this study consists of 35 employees from the Regional Secretariat of Labuhanbatu Regency. The entire population in this study will be used as the sample, which is 35 employees. Multiple linear regression analysis was tested using partial (t) test, simultaneous (F) test, and coefficient of determination. The research results prove that both partially and simultaneously, Job Satisfaction, Compensation, Work Environment, Work Delay, and Organizational Culture have a positive and significant effect on Employee Performance at Pudam Tirtabina, Labuhanbatu Regency.